(3OjhGf HGeNQeIs - (3YeQ Hf YHO Gddg HGeNQeI GdgLQGfj GdTjHGfj GdMVQej,J (B952 (3g` s ((3GdSjO YHO Gddg Hf eMeO Hf Rjf (B( (3GdMHTi (B) s)
(3ChdgG (B:s
(3GdMeO ddg GdeSHd Ydi bdhH GdYGQajf eYQaJg hMceg GdHGA (B: (3fGUQ Cjf GdPi UGHc YSi Gddg jUjHg s
(3BNQgG (B:s
(3BNQg ai bGajI GdjGA(B: (3dbJfGU GdHhGOi GdHGOjGJ GdfhGjg Pi JhGajc ef ZjQ ELJgGO s
(3eQJH Ydi GdbhGais
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B213s
Keywords: (3GdCOHs